Survival analysis of patients with bladder cancer, life table approach - Abbas Rezaianzadeh; Abolfazl Mohammadbeigi; Jafar Mobaleghi; Narges Mohammadsalehi (Wolters Kluwer Medknow Publications, 2012)
Background: Bladder cancer is the fourth most common malignancy in men and the eighth most common in women. It causes 8% of all malignancies in men and 3% of all malignancies in women. The trend of bladder cancer is increasing in Iran. This study was conducted to estimate the survival rate of bladder cancer based on life table method. Materials and Methods: In this study, at first, data were collected based on individual variables of 514 patients suffering from bladder cancer and referred them to cancer registry center of Shiraz University of Medical Sciences from 2001-2009. Data were collected at two stages and analyzed by life table method and Wilcox on test. Significant level considered at 0.05. Results: Our findings showed that probability of survival accumulation at the end of 1, 3, 5, 10 years in patients with bladder cancer were equal to 0.8989, 0.7132, 0.5752 and 0.2459 respectively. There was significant difference in survival rate among age groups and treatment types (P < 0.05). However, we did not observe any difference in survival time based on smoking (P = 0.578), alcohol (P = 0.419) and education level (P = 0.371) of patients. Conclusion: The overall survival rate of bladder cancer in the present study was less than other areas. Patients' age and treatment type were the influential factor in survival time. So continuous screening for early diagnosis suggested for older people.